Channel Assignment Based on Routing Decisions (CARD): Traffic-Dependent Topology Control for Multi-Channel Networks - DA SILVA, LUIZ (My University, 2009)
Dynamic spectrum access (DSA) holds the promise for more efficient utilization of the spectrum, while requiring greater cooperation between PHY, MAC, and NET layers to allocate resources and dynamically react to changing network conditions. In this paper, we propose Channel Assignment based on Routing Decisions (CARD), a mechanism that combines channel assignment and topology control so that at any given time the cognitive network self-organizes into the topology that is best suited to support the current offered traffic. CARD is a distributed mechanism, and each network node relies on local information only. We show that CARD results in an improvement in route length (and, thus, end-to-end delay), aggregate network capacity, and, in some situations, energy efficiency.
PUBLISHED
Keywords: Computer science; Dynamic spectrum access (DSA)